THE IMPACT OF USING ARTIFICIAL INTELLIGENCE (DEEPL) ON ELEVENTH GRADE STUDENTS’ WRITING SKILLS AT MAN KARANGASEM - Maryam, Syfa Wahida; Santosa, Made Hery; Dewi, Kadek Sintya (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
The purpose of this study is to determine whether the use of DeepL in learning can have an impact on students' ability to write English and to find out how the implementation of DeepL impacts students' writing ability. This study uses a mixed method in helping researchers to obtain data, namely Quasi Experimental Non-Equivalent (Pretest and Posttest) Control Group Design on quantitative pre-test and post-test student provision as a form of quantitative data and interviews for qualitative data. The sample involved in this study was 56 students who were divided into two groups: the experimental group, which was the group that received the treatment and also the control group where the researcher conducted conventional learning activities. The use of deep learning in English learning does not provide sufficient impact even though in the acquisition of interview data students have an interest in DeepL. As a result of this research, the researcher assumes that the use of AI-based applications in learning still needs more development and attention.Keywords: Artificial Intelligence, Deep, writing skills